2008
DOI: 10.1097/aog.0b013e31818c91dc
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Developmental Delays in a Down Syndrome Mouse Model

Abstract: Objective To estimate whether prenatal treatment with neuroprotective peptides prevent the developmental delay and the glial deficit in the Ts65Dn mouse model for Down syndrome, and to explore the peptides effects on achievement of normal development. Methods Pregnant Ts65Dn females were randomly assigned to NAPVSIPQ+ SALLRSIPA or control and were treated by investigators blinded to treatment and genotype on gestational days 8–12. Offspring were tested from postnatal day (P) 5 to 21 for motor and sensory mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 22 publications
(32 reference statements)
5
34
0
3
Order By: Relevance
“…12 In a mouse model for Down syndrome, prenatal treatment with NAPV-SIPQ and SALLRSIPA reversed developmental deficits in newborn pups. 26 In normal animals, NAPV-SIPQ and SALLRSIPA have been shown to enhance learning. 27 However, despite the well-documented neurotrophic and neuroprotective actions of NAPV-SIPQ and SALLRSIPA in numerous abnormalities, the molecular mechanisms and signaling pathways that mediate these effects are not well understood, and recent studies of hippocampal cultures found that activity-dependent neurotrophic factor alters glutamate release and NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…12 In a mouse model for Down syndrome, prenatal treatment with NAPV-SIPQ and SALLRSIPA reversed developmental deficits in newborn pups. 26 In normal animals, NAPV-SIPQ and SALLRSIPA have been shown to enhance learning. 27 However, despite the well-documented neurotrophic and neuroprotective actions of NAPV-SIPQ and SALLRSIPA in numerous abnormalities, the molecular mechanisms and signaling pathways that mediate these effects are not well understood, and recent studies of hippocampal cultures found that activity-dependent neurotrophic factor alters glutamate release and NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this effect, prenatal treatment (i.p. injections to Ts65Dn pregnant females in the period E8-E12) with NAP (20 µ g) plus SAL (20 µ g) prevents the delay of neurodevelopmental milestones in trisomic offspring (Toso et al, 2008 ). While treatment does not prevent VIP up-regulation, it appears to improve the reduced levels of ADNP.…”
Section: Interventions Targeted To Neuroprotectionmentioning
confidence: 96%
“…These peptides were derived by fusing two other neuroprotective peptides, NAP (NAPVSIPQ) and activity-dependent neuroprotective factor-9 (ADNF9, SALLRSIPA). ADNF9 and NAP protect neurons from a variety of neurotoxic insults by unknown mechanisms [35][36][37][38]. Thus, these fusion peptides were prepared to examine their in vitro and in vivo activities.…”
Section: Structure Comparisonmentioning
confidence: 99%